Implementation of Sustainable Development Towards Environmental Ecosystem in Melaka River Basin - Ang, Kean Hua; Gani, Paran; Yusof, Junaidah; Halim, Noor Hafizah Abdul; Yahya, Sayzwani binti (European Publisher, 2019)
Different form of development planning and management approaches have been applied and implemented by many countries in river basins for the past decades. Nevertheless, the outcomes are disappointing. This study aims to explore the local people awareness towards environmental ecosystem by adopting sustainable development. A quantitative method through the questionnaire was reported in two parts. Part A was the environmental ecosystem study while Part B was the sustainable development study. Random sampling technique with 100 respondents was targeted within Melaka River basin. Descriptive analysis showed majority of the respondents were positively agreed that industrial, residential, commercial and agricultural activities would contribute water contamination to the Melaka River basin. Meanwhile, sustainable development of law and regulation, policy, environmental ethics, as well as environmentally friendly were likely to have skewed graph shift towards right hand side, whereby respondents believed that these sustainable development had a possibility to control and manage the river pollution in Melaka River basin. Correlation analysis showed sustainable development positively impacts on the environmental ecosystem in Melaka River basin. In conclusion, implementing and adapting the sustainable development approach would indirectly preserve and conserve the environmental ecosystem before anthropogenic activities take place to destruct the water quality in Melaka River basin.